Static and Dynamic Analyses of Spindle Collet Made of Different Materials Using Finite Element Modeling - Omar, Mohd Hazri; Allias, Mohd Fadzil; Radzi, Rohaizan; Abdul Halim, Mohamad Nazri (Universitas Muhammadiyah Yogyakarta, 2024)
The spindle collet, a critical component in various machine tools, plays a pivotal role in determining the success of machining operations. This paper aims to study the static and dynamic parameters of collet structures made from three different materials using the finite element method. A three-dimensional model and computer simulation were conducted in Autodesk Inventor software. Simulations are performed using identical boundary conditions and mesh size. Static analysis is performed with varied applied forces where total deformation and Von Mises stress are measured. For the dynamic analysis, the natural frequencies and mode shapes are measured up to the first five modes. The variations in stress is minimal when the material is altered. The magnitude of deformation varies significantly with changes in material. The relative deformation values demonstrate that carbon steel deforms more than alloy steel by almost 3%, while stainless steel deforms more than alloy steel by 6%. Materials with higher Young's modulus and lower density have been found to increase the natural frequencies, reducing total deformation and von Misses stress. The use of alloy steel in the industry offers an advantage over the other two materials. The results provide improved insight into the appropriate materials for the collet.